Investigating Length and Mean-Fuzzy Subalgebras in Sheffer Stroke Hilbert Algebras (European Journal of Pure and Applied Mathematics, 2025)
The aim of this paper is to introduce the notions of the length and the mean of an interval-valued fuzzy structure in Sheffer stroke Hilbert algebras. The notions of length-fuzzy subalgebras and mean-fuzzy subalgebras of Sheffer stroke Hilbert algebras are introduced, and related properties are investigated. Characterizations of length-fuzzy subalgebras and mean-fuzzy subalgebras are discussed. Relations between length-fuzzy subalgebras (resp., mean-fuzzy subalgebras) and subalgebras are established. Moreover, we discuss the relationships among length-fuzzy subalgebras (resp., mean-fuzzy subalgebras) and upper and lower-level subsets of the length (resp., mean) of an interval-valued fuzzy structure in Sheffer stroke Hilbert algebras.
Keywords: Sheffer stroke Hilbert algebra; subalgebra; length-fuzzy subalgebra; mean-fuzzy subalgebra